Incidence, characteristics, and treatments of peripheral neuropathy in multiple myeloma patients receiving bortezomib (velcade) - S. S. Bessmeltsev; E. V. Karyagina; L. V Stelmashenko; N. V. Stepanova; E. R. Machulaiten; G. N. Salogub; I. A. Skorokhod; N. V. Medvedeva; E. I. Podoltseva; L. M. Matyukhina; A. S. Nizamutdinova; K. M. Abdulkadyrov (Онкогематология)
The characteristics of peripheral neuropathy (PN), its incidence and a possibility of relieving in multiple myeloma (MM) patients receiving bortezomib are presented. A hundred and twenty-four patients with recurrent/refractory MM and 14 primary patients were followed up. PN more commonly occurred after 3—5 cycles of bortezomib therapy. Grade > 2 PN was observed in 29% of the patients. The cumulative dose of bortezomib was 15.6 to 26 mg/m2. After 6—8 cycles the incidence of PN was also high. There was a correlation between the cumulative dose of bortezomib and the incidence of PN (R = 0.927; p < 0.0009). A correlation was also found between the incidence of PN and prior vincristine-containing treatment regimens (VAD scheme). Overall, PN was identified in 54% of the patients. Treatment of PN with gabapentin, pregabalin, vitamins B, and α-lipoic acid was effective. PN resolved to the baseline levels or the patients’ condition improved in 72% of the patients, the median time taken for resolution or improvement being 114 days. It is necessary to reduce the dose of bortezomib or to discontinue the drug temporarily in order to relieve the symptoms of neuropathy.